Transformacja Polski a integracja z Unią Europejską - Płowiec, Urszula (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
After 15 years of transformation process of Poland in spite of numerous difficulties and failures -the Polish state, society and market economy are consolidated. It is partially the effect of the aspiration and then of the membership in the EU, especially due to its pressure on render the functioning of institutions and the economy more efficient, as well as due to its technical and financial assistance. The accomplished transformation is however asymmetric: achievements in the functioning of markets (except for labour) and enterprises are larger and deeper than in the functioning of legislative and judiciary authorities, other institutions of public sector and society. In order to prepare Poland to the global challenges related to the growing competition of Asian giants and to knowledge based economy it is necessary to reconstruct the public sector and the mentality of society. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 255-264